Implementasi Tridharma Perguruan Tinggi melalui Proyek Redesain Gedung Gereja di Bandung - Agus Dody Purnomo; Agustinus Nur Arief Hapsoro; Yap, Angel Brielle; Kahagi, Chelsea Angelica; Ranteallo, Kezia (Yayasan Literasi Sains Indonesia, 2024)
Universities play an important role in advancing the nation. This role is described in the Tridharma of Higher Education, including: teaching, research, and community service. Each dharma has its own form and goal but is interrelated. Lecturers and students can collaborate in implementing the Tridharma of higher education. The aim of the paper is to examine the implementation of the Tridharma in higher education through collaborative projects. The method uses the design method with data collection, surveys, interviews, and measurements of existing buildings. The next stage is analysis and synthesis to drafting the design concept. The Efrata Baptist Church in Bandung acts as the target community. Design projects are interesting learning tools for students. Students are able to develop their potential and explore lecture material through real cases. Design is also related to research activities. Research provides knowledge for design while design provides insight for future problem solving. The results of collaborative projects between lecturers and students are concrete evidence of community service activities. The output result is a redesign preliminary drawing that will be used in carrying out the renovation of the church building.